Electrical property inspection tool

JP7640222B2Active Publication Date: 2025-03-05DEXERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2019124819
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-07-03
Publication Date
2025-03-05
Estimated Expiration
2039-07-03

AI Technical Summary

Benefits of technology

【0016】 本技術によれば、ファインピッチに形成されたパッドやバンプの電気特性の検査に対し、優れた耐久性を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640222000002
    Figure 0007640222000002
  • Figure 0007640222000003
    Figure 0007640222000003
  • Figure 0007640222000004
    Figure 0007640222000004
Patent Text Reader

Abstract

To provide an inspection tool for inspecting electrical characteristics having excellent durability to the inspection for electrical characteristics of pads or bumps which are formed at fine pitches.SOLUTION: An inspection probe sheet 1 comprises: a flexible sheet 10 having a plurality of through electrodes 14 which have concave parts 12 on a first surface 11a and have convex parts 13 on a second surface 11b; and conductive bumps 20 which are arranged in the concave parts 12 of the through electrodes 14 and include thermoplastic resin having a bending elastic modulus of 1300 MPa s or more and 2600 MPa s or less and conductive particles and in which the conductive particles are connected in a thickness direction of the flexible sheet 10. By making the conductive bumps 20 contact pads or bumps and making the through electrodes 14 contact wire probes, excellent durability can be obtained in the inspection of electrical characteristics of the pads and the bumps formed at fine pitches.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a test tool for the electrical characteristics of electronic components such as wafers, chips, and packages. [Background technology]

[0002] Currently, evaluation of the electrical characteristics of semiconductor devices at the wafer level is performed using a probe card by directly contacting probes with conductive pads and bumps formed on the front and back surfaces of the wafer (see, for example, Patent Document 1).

[0003] This method makes it possible to carry out inspection before packaging or before three-dimensional mounting.

[0004] However, in order to remove the oxide film on the pad surface of the wafer, the surface is scratched before the probe test is performed, and this can result in products that pass the test being rejected due to damage caused by the test after they are mounted. As the pad size becomes smaller, the impact of scratches during the test, which can cause defects during bump formation and mounting, becomes greater. In particular, in recent years, as semiconductor chips have become increasingly fine-pitched, scratches during the test have become an increasingly big problem.

[0005] For bare chips and packages, a handler test using a rubber connector is performed. As a rubber connector that serves as an inspection probe sheet, for example, an anisotropic conductive sheet in which magnetically oriented conductive particles are arranged so as to penetrate the elastomer sheet in the thickness direction has been proposed (for example, see Patent Document 2).

[0006] The inspection probe sheet described in Patent Document 2 has difficulty in dealing with fine pitches because the conductive particles are linked in the in-plane direction when they are magnetically oriented in the rubber elastic elastomer resin. In addition, although a frame is attached to surround the periphery in order to improve durability, the elastomer resin inside the frame is a material that easily expands and contracts due to thermal expansion, which causes problems with reduced durability and inspection failures due to contact misalignment (positional misalignment). In particular, positional misalignment during heat cycle tests and the like is fatal, making it difficult to deal with future finer pitches.

[0007] In addition, it is generally difficult to manufacture fine-pitch rubber connectors, which are made by disposing conductive material in elastomer resin, and it is difficult to manufacture inspection connectors with a level of 200 μmP or less. For this reason, inspections are currently carried out on packages after assembly, which results in extremely poor yields and makes it difficult to reduce prices.

[0008] As a method for solving these problems, Patent Document 3 describes that by using an inspection probe sheet 100 having a plurality of through electrodes 114 each having a recess 112 on a first surface 111a of a flexible sheet 110 and a protrusion 113 on a second surface 111b as shown in FIG. 4, and disposing a conductive elastomer 120 in the recess 112, electrical characteristics can be inspected even if an oxide film is formed on pads or bumps formed at a fine pitch.

[0009] However, in the method described in Patent Document 3, although it is possible to inspect the electrodes formed in the fine pitch, the electrodes come into direct contact with the conductive elastomer part, so as the inspection is repeated, the conductive elastomer part gradually deteriorates, the conductive particles and binder fall off or break, and the resistance value increases. In addition, while these inspections usually require at least 10,000 repeated uses, the current situation is that the method described in Patent Document 3 can only last less than 1,000 times. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2009-042008 A [Patent Document 2] JP 2006-024580 A [Patent Document 3] JP 2018-141652 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present technology is intended to solve the above-mentioned problems, and provides an electrical characteristics inspection tool with excellent durability for inspecting the electrical characteristics of pads and bumps formed at a fine pitch. [Means for solving the problem]

[0012] As a result of intensive research, the inventors of the present technology have discovered a method for manufacturing a flexible sheet having a through hole penetrating a first surface and a second surface, a through electrode half-formed in the through hole, the flexible sheet having a recessed portion recessed in the first surface, and a conductive film having a predetermined bending elastic modulus and a conductive material disposed in the recessed portion. And melting point of 160℃ to 200℃ The inventors have found that by using an inspection tool comprising a polyamide having the above formula (I) and conductive particles, the conductive particles being connected in the thickness direction of the flexible sheet, it is possible to obtain excellent durability in inspection of the electrical properties of pads and bumps formed at a fine pitch.

[0013] That is, the electrical characteristic inspection jig according to the present technology includes a flexible sheet having a through hole penetrating a first surface and a second surface, a through electrode half-formed in the through hole, the through hole having a recess recessed in the first surface, and a flexible sheet having a bending modulus of elasticity of 1300 MPa or more and 1600 MPa or less, the bending modulus being 1300 MPa or more and 1600 MPa or less, the bending modulus being 1300 MPa or more and 1600 MPa or less, the bending modulus being 1600 MPa or more and the bending modulus being ... more and the bending modulus being 1600 MPa or more And melting point of 160℃ to 200℃ and conductive bumps including conductive particles connected in the thickness direction of the flexible sheet.

[0014] In addition, a method for manufacturing an inspection jig according to the present technology includes the steps of: forming a through electrode in a flexible sheet having a through hole penetrating a first surface and a second surface, the through hole having a recess recessed in the first surface; and forming a through electrode in the recess having a bending elastic modulus of 1300 MPa or more and 1600 MPa or less. And melting point of 160℃ to 200℃ and a heating step of melting the polyamide particles and connecting the conductive particles in the thickness direction of the flexible sheet.

[0015] In addition, a method for inspecting electrical characteristics according to the present technology includes a flexible sheet having a through hole penetrating a first surface and a second surface on an electrode surface of an object to be inspected, the through hole having a through electrode half formed in the through hole penetrating a first surface and a second surface, the flexible sheet having a recess recessed in the first surface, and a conductive material having a bending modulus of elasticity of 1300 MPa or more and 1600 MPa or less, which is disposed in the recess. And melting point of 160℃ to 200℃ The method includes a pasting process of pasting an inspection probe sheet containing polyamide having a structure and conductive particles, the conductive particles being connected in the thickness direction of the flexible sheet, and bringing the conductive bumps into contact with electrodes of the object to be inspected, and a testing process of pressing a probe against a through electrode from the other side of the inspection probe sheet to test electrical characteristics. Effect of the Invention

[0016] According to the present technology, excellent durability can be obtained when testing the electrical characteristics of pads and bumps formed at a fine pitch. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a cross-sectional view showing an example of an inspection probe sheet according to the present embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a flexible sheet having a plurality of through electrodes each having a recess. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates a test process for testing electrical characteristics using the test probe sheet according to the present technology. [Figure 4]FIG. 4 is a cross-sectional view showing an example of a conventional inspection probe sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, embodiments of the present technology will be described in detail in the following order. 1. Electrical property inspection tool 2. Manufacturing method of inspection jig 3. Electrical characteristics inspection method

[0019] <1. Electrical property inspection tool> The electrical characteristic inspection tool according to the present technology is: A through electrode is half-formed in a through hole penetrating the first surface and the second surface, and a recess is formed in the first surface. A flexible sheet; Recess It is located at 1300 MPa More than 2600 MPa This is a so-called inspection probe sheet that contains a thermoplastic resin having the following bending elastic modulus, conductive particles, and conductive bumps in which the conductive particles are connected in the thickness direction of the flexible sheet.

[0020] When the flexural modulus is smaller than the lower limit, the durability of the conductive bump may not be sufficiently improved, and when the flexural modulus is larger than the upper limit, the conductive bump may crack when subjected to an impact. In this specification, the flexural modulus of the thermoplastic resin refers to the flexural modulus measured in accordance with JIS K 7071.

[0021] According to the inspection probe sheet of the present technology, by contacting the pads or bumps with the conductive bumps and contacting the wire probes with the through electrodes, it is possible to obtain excellent durability for testing the electrical properties of the pads and bumps formed at a fine pitch.

[0022] Fig. 1 is a cross-sectional view showing an example of an inspection probe sheet according to the present embodiment, and Fig. 2 is a cross-sectional view showing an example of a flexible sheet having a plurality of through electrodes having recesses. The inspection probe sheet 1 according to the present embodiment has recesses 12 on a first surface 11a and protrusions 13 on a second surface 11b. It was formed like thisA flexible sheet 10 having a plurality of through electrodes 14; Recess 12 It is located at 1300 MPa More than 2600 MPa The flexible sheet is provided with conductive bumps 20 that contain a thermoplastic resin having the following bending elastic modulus and conductive particles, the conductive particles being connected in the thickness direction of the flexible sheet.

[0023] The flexible sheet 10 is preferably made of a material that is flexible and insulating, has a low coefficient of thermal expansion, and is highly heat resistant. Examples of materials for the flexible sheet 10 include polyimide, polyamide, polyethylene naphthalate, biaxially oriented polyethylene terephthalate, and liquid crystal polymer. These materials are preferred because they have better dimensional stability than elastic elastomers, are less likely to cause electrical continuity problems due to misalignment in thermal cycle tests, and are also highly durable. Of these, it is preferred to use polyimide, which has excellent heat resistance.

[0024] If the flexible sheet 10 is too thin, the durability is poor, so the thickness is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. If the flexible sheet 11 is too thick, it becomes difficult to form the through electrodes, so the thickness is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less.

[0025] The through electrodes 14 exist independently and are insulated from adjacent through electrodes, and may be formed in advance to match the positions of pads or bumps on the object to be inspected, or may be formed at predetermined intervals.

[0026] The through electrodes 14 are formed in the thickness direction of the flexible sheet 10, and have recesses 12 recessed into the first surface 11a of the flexible sheet 10. The lower limit of the depth of the recesses 12 is preferably 20% or more of the thickness of the flexible sheet 10, more preferably 40% or more, and even more preferably 60% or more. The upper limit of the depth of the recesses 12 is preferably 90% or less of the thickness of the flexible sheet 10, more preferably 80% or less, and even more preferably 70% or less. This allows the thickness of the conductive bumps 20 to be increased, and therefore the amount of movement when the inspection probe sheet 1 is pressed down can be increased, and the height of the pads and bumps can be accommodated.

[0027] In addition, the surface of the recess 12 of the through electrode 14 is preferably plated with Ni / Au plating, Ni / Pd plating, Ni / Pd / Au plating, or the like, and is covered with a metal plating film. This improves adhesion to the conductive bump 20 due to the anchor effect of the recess 12, thereby improving durability and improving conductivity with the conductive bump 20.

[0028] The through electrode 14 has a protrusion 13 protruding from the second surface 11b of the flexible sheet 10. The lower limit of the height of the protrusion 13 is preferably 10% or more of the thickness of the flexible sheet 10, more preferably 20% or more, and even more preferably 30% or more. The upper limit of the height of the protrusion 13 is preferably 60% or less of the thickness of the flexible sheet 10, more preferably 50% or less, and even more preferably 40% or less. The surface of the protrusion 13 of the through electrode 14 is preferably plated with Ni / Au plating, Ni / Pd plating, Ni / Pd / Au plating, or the like, and is preferably covered with a metal plating film. This provides excellent durability against the tip of the wire probe and the pads and bumps of the test object.

[0029] The through electrode 14 is made of a conductive metal or alloy, and is preferably made of a metal or alloy such as copper or nickel. The through electrode 14 preferably has a so-called "tapered shape" in which the diameter increases from the first surface 11a to the second surface 11b of the flexible sheet 10. This allows the diameter of the tip of the wire probe to be made larger than the size of the pad or bump of the test object.

[0030] The conductive bumps 20 protrude from the first surface 11a of the flexible sheet 10. If the protruding height of the conductive bumps 20 is too low, the amount of movement when the inspection probe sheet 1 is pressed down becomes small, making it difficult to follow the variation in height of the pads and bumps. For this reason, the protruding height of the conductive bumps 20 is preferably 50% or more of the average particle diameter of the conductive particles, more preferably 100% or more, and even more preferably 150% or more. In addition, if the protruding height of the conductive bumps 20 is too high, the protruding portion will break, so it is preferably 400% or less of the average particle diameter of the conductive particles, more preferably 300% or more, and even more preferably 250% or less.

[0031] The conductive bumps 20 are formed from a conductive binder containing a thermoplastic resin and conductive particles. MPa More than 2600 MPa The bending modulus is preferably 1300 or less. MPa More than 1600 MPa The following flexural modulus is available: 。 The lower limit of the melting point of the thermoplastic resin is preferably 150° C. or higher, more preferably 160° C. or higher, and the upper limit of the melting point of the thermoplastic resin is preferably 220° C. or lower, more preferably 200° C. or lower. This allows the thermoplastic resin to soften at high temperatures and have excellent moldability, making it possible to form conductive bumps at fine pitches. Examples of such thermoplastic resins include polyamide (polyamide 12, polyamide 66, polyamide 6, etc.), polyacetal, polycarbonate, modified polyphenylene ether, polybutylene terephthalate, polyester, PMMA, etc.

[0032] The total content of the thermoplastic resin and the conductive particles in the conductive bump 20 is preferably 85 wt% or more, more preferably 90 wt% or more, and even more preferably 95 wt% or more, so that the conductive bump 20 can have the excellent durability of the thermoplastic resin.

[0033] The conductive particles are chained from the recess 12 of the through electrode 14, with their extreme ends exposed from the outermost surface of the thermoplastic resin, and the extreme ends of the conductive bump 20 and the protrusion 13 of the through electrode 14 are electrically connected.

[0034] The conductive particles may be any conductive particles, and are preferably made of magnetic metals such as nickel, cobalt, and iron, or particles in which a magnetic metal is plated on a resin core or inorganic core particle. The conductive particles may be plated with Ni / Au plating, Ni / Pd plating, Ni / Pd / Au plating, or the like, and may be covered with a metal plating film. When the conductive particles contain a magnetic metal, applying a magnetic field when filling the recesses 12 of the through electrodes 14 with the conductive binder can easily chain the conductive particles together, linking the through electrodes 14 to the conductive particles on the resin surface, and establishing electrical continuity.

[0035] The smaller the average particle diameter of the conductive particles, the smaller the pads and bumps that can be accommodated. Therefore, the upper limit of the average particle diameter of the conductive particles is preferably 15 μm or less, more preferably 8 μm or less, and even more preferably 4 μm or less, and the lower limit of the average particle diameter of the conductive particles is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more.

[0036] The conductive particles may be spherical, polygonal, or spiky in shape, and when the conductive particles are polygonal or spiky in shape, they can more easily break through the oxide film of the pads or bumps of the test object.

[0037] In the above-described inspection probe sheet, the through electrode 14 has the convex portion 13 protruding from the second surface 11b of the flexible sheet 10, but the present invention is not limited to this and may have a recessed portion recessed into the second surface 11b of the flexible sheet 10. By having the through electrode 14 have a recessed portion on the second surface 11b of the flexible sheet 10, the tip of the wire probe fits into the recessed portion, and the wire probe can be prevented from falling off the through electrode.

[0038] <2. Manufacturing method of inspection jig> The manufacturing method of the inspection jig according to the present technology includes: A step of forming a through electrode in a flexible sheet having a through hole penetrating a first surface and a second surface, so as to have a recessed portion recessed in the first surface; 1300 MPa More than 2600 MPa The method includes a filling step of filling a conductive binder containing thermoplastic resin particles made of a thermoplastic resin having the following flexural modulus and conductive particles, and a heating step of melting the thermoplastic resin particles and connecting the conductive particles in the thickness direction of the flexible sheet. This makes it possible to obtain an inspection probe sheet that has excellent durability for inspection of the electrical properties of pads and bumps formed at a fine pitch.

[0039] Next, a more specific manufacturing method of the inspection probe sheet will be described with reference to Figures 1 and 2. First, a through hole is formed in a flexible sheet by laser processing, and a through electrode is half-formed in the through hole by electrolytic plating to form a recess. It is also preferable to plate the through electrode and the side surface of the recess with Ni / Au plating, Ni / Pd plating, Ni / Pd / Au plating, or the like, and cover them with a metal plating film.

[0040] Next, using a screen printer, In recess 12 The conductive binder in which the thermoplastic resin particles and conductive particles are dispersed is printed evenly. Recess 12 A conductive binder may be evenly applied to the surface.

[0041] The lower limit of the average particle size of the thermoplastic resin particles is preferably 1 μm or more, more preferably 3 μm or more, and the upper limit of the average particle size is preferably 10 μm or less, more preferably 5 μm or less, which allows excellent filling properties into the recesses 12 to be obtained.

[0042] It is preferable to adjust the viscosity of the conductive binder by a solvent. The viscosity of the solvent is preferably 1000 mPa·s to 10000 mPa·s. If the viscosity of the solvent is too low or too high, printing may become difficult.

[0043] The lower limit of the viscosity of the conductive binder at 25° C. is preferably 35 Pa s or more, more preferably 40 s or more, and the upper limit of the viscosity of the conductive binder at 25° C. is preferably 60 Pa s or less, more preferably 50 Pa s or less. This allows the conductive binder to be printed so as to protrude from the first surface 11a of the flexible sheet 10.

[0044] Next, a magnetic field is applied from the protrusion 13 side of the through electrode 14 of the flexible sheet. As a result, if the conductive particles contain a magnetic metal, the conductive particles are easily chained together to connect from the through electrode to the conductive particles on the surface layer of the thermoplastic resin, thereby achieving electrical continuity.

[0045] Next, in a state where a magnetic field is applied to fix the conductive particles, the sheet is heated in an oven at a temperature of 100 to 200° C. for 0.5 to 3 hours, and further heated at a temperature of 150 to 250° C. for 1 to 4 hours. This makes it possible to obtain a probe sheet for testing in which conductive bumps 20 are formed by filling the recesses 12 of the through electrodes 14 with the conductive binder.

[0046] <3. Electrical characteristics inspection method> The electrical characteristics inspection method using this technology involves: A through electrode is half-formed in a through hole penetrating the first surface and the second surface, and a recess is formed in the first surface. A flexible sheet; Recess It is located at 1300 MPa More than 2600 MPaThe method includes a pasting step (A) of pasting an inspection probe sheet including a thermoplastic resin having the following bending elasticity and conductive particles, the conductive particles being connected in the thickness direction of the flexible sheet, and bringing the conductive bumps into contact with electrodes of an object to be inspected, and a testing step (B) of pressing a probe against the through electrodes from the other side of the inspection probe sheet to test electrical characteristics. This makes it possible to demonstrate excellent durability in testing the electrical characteristics of pads and bumps formed at a fine pitch.

[0047] An example of the object to be inspected is a semiconductor device. The semiconductor device may be at any of the following levels: a wafer level formed on a wafer, an individual chip level, and a package level after packaging. In the following, a method for inspecting electrical characteristics of a semiconductor device at the chip level will be described, including an attachment step (A), an inspection step (B), and a peeling step (C) of peeling the inspection probe sheet from the semiconductor device after the inspection step. Note that the inspection probe sheet is the same as the inspection probe sheet described above, and therefore a description thereof will be omitted here.

[0048] [Attachment process (A)] In the attachment step (A), the inspection probe sheet is attached to the electrode surface of the semiconductor device, and the conductive bumps are brought into contact with the bumps of the semiconductor device. In addition, in the attachment step (A), it is preferable to press the inspection probe sheet. As a result, even if an oxide film is formed on the bumps of the semiconductor device, the conductive particles in the conductive bumps break through the oxide film, so that the electrical characteristics can be inspected.

[0049] [Inspection process (B)] FIG. 3 is a cross-sectional view that illustrates a test process for testing electrical characteristics using the test probe sheet according to the present technology.

[0050] 3, in the inspection process (B), a wire probe 40 is pressed against the convex portion 13 of the through electrode 14 of the flexible sheet 10, and the bump 31 of the semiconductor device 30 is brought into contact with the conductive bump 20 arranged in the concave portion 12 of the through electrode 14 to inspect the electrical characteristics.

[0051] The wire probe 40 is a probe for inspecting electrical characteristics, and is preferably erected perpendicular to the electrode surface of the through electrode as shown in Fig. 3. The wire probe 40 may have a plurality of pins arranged thereon. The tip shape of the wire probe 40 is not particularly limited, and may be a spherical surface, a flat surface, a concave surface, a sawtooth surface, or the like. When the through electrode does not protrude, the tip diameter of the wire probe 40 is preferably smaller than the width of the electrode, but when the electrode of the through electrode protrudes, the tip diameter may be larger than the width of the electrode as long as it does not cause a short circuit with an adjacent electrode.

[0052] The electrical characteristics are inspected by measuring the characteristics of, for example, transistors, resistors (electrical resistance), capacitors, and the like.

[0053] [Peeling process (C)] In the peeling process (C), the inspection probe sheet is peeled off from the semiconductor device. The semiconductor device may be washed after the peeling of the inspection probe sheet. The peeled inspection probe sheet can be used multiple times. <3. Examples> EXAMPLES

[0054] Examples of the present technology will be described below. In the examples, an inspection tool for electrical characteristics was produced and used to perform a continuity test on a bare chip. Then, the presence or absence of pad damage and durability after the continuity test were evaluated. Note that the present technology is not limited to these examples.

[0055] [Measurement of the viscosity of conductive binder] The initial viscosity of the conductive binder at 25° C. was measured using a rheometer (manufactured by HAAKE).

[0056] [Evaluation of pad scratches] After the continuity test, the solder bumps were visually inspected for damage.

[0057] [Durability evaluation] As a durability test, a continuity test was repeated 10,000 times, and the initial test resistance value and the test resistance value after the durability test were measured. <Example 1>

[0058] [Fabrication of flexible sheet with through electrodes] A polyimide sheet (product name: Esperflex, copper thickness 8 μm, polyimide thickness 25 μm, manufactured by Sumitomo Metal Mining Co., Ltd.) with copper laminated on both sides was laser processed to form through holes with a lattice spacing of 60 μmP, and through electrodes were formed in the through holes by copper plating using electrolytic plating. The through electrodes were half-formed, with a recess of a groove 15 μm in the thickness direction from the surface of the sheet. Next, after plating with nickel and gold, the copper layers on the front and back were removed by etching to create a flexible sheet. Nickel and gold plating was also formed on the polyimide surface on the side of the recess.

[0059] [Preparation of conductive binder] Conductive particles were prepared by applying a gold plating layer by electroless displacement plating to the surface of Ni / Ag-plated resin core particles (manufactured by Sekisui Chemical Co., Ltd.) with an average particle size of 3 μm. In addition, nylon 12 fine particles (SP-500, manufactured by Toray Industries, Inc., with a bending modulus of 1.4 μm) with an average particle size of 5 μm were used as thermoplastic resin particles. GPaA conductive binder was prepared by mixing 100 parts by mass of thermoplastic resin particles with 200 parts by mass of conductive particles, adding diethylpentanediol (boiling point 264°C, viscosity 1000mPa s) as a solvent and mixing uniformly using a planetary agitator mixer. The viscosity of the conductive binder was 43 Pa s. The conductive binder was in a state where nylon microparticles and conductive particles were dispersed in the solvent.

[0060] [Creating inspection probe sheets] Using a screen printer (manufactured by Newlong Precision Industry Co., Ltd.), the conductive elastomer dispersion was evenly printed into the recesses of the through electrodes of the flexible sheet so that the conductive elastomer protruded 10 μm from the surface of the sheet. Next, the flexible sheet was placed on a permanent magnet and left in an open at 200°C for 1 hour to dry the solvent and produce a probe sheet for testing. The conductive bumps formed from the conductive elastomer dispersion were in a state where the nylon 12 fine particles had melted and the conductive particles had bonded together to form an integrated unit.

[0061] [Continuity check] A 6 mm square bare chip (Dexerials evaluation substrate) with 20 μm high, 30 μm diameter solder-capped copper pillar bumps (hereinafter referred to as solder bumps) arranged at 60 μm pitch was used as the evaluation bare chip, and a 30 μm diameter wire probe (Tespro) was used to perform a continuity resistance test. More specifically, as shown in Figure 3, the circuit surface of the evaluation pair chip was aligned with one electrode surface of the inspection probe sheet and pressed, and the wire probe was brought into contact with the opposite electrode surface of the inspection probe sheet with a load of 5 g / pin to perform a continuity test. Table 1 shows the presence or absence of scratches on the solder bumps after the continuity test, and the continuity resistance values ​​before and after the durability test.

[0062] <Example 2> A conductive binder was prepared in the same manner as in Example 1, except that the solvent was changed to "Nika MHDJ" (dihydroterpineol type, boiling point 220°C, viscosity 3000 mPa s, manufactured by Nikko Aromatic Chemicals). The viscosity of the conductive binder was 49 Pa s. The conductive binder was in a state where nylon fine particles and conductive particles were dispersed in the solvent.

[0063] A probe sheet was also produced in the same manner as in Example 1. The conductive bumps formed from the conductive binder were in a state in which the nylon 12 fine particles had melted and the conductive particles had bonded together to form an integrated structure. A continuity test was then carried out in the same manner as in Example 1. Table 1 shows the presence or absence of damage to the solder bumps after the continuity test, and the continuity resistance values ​​before and after the durability test.

[0064] <Comparative Example 1> A conductive binder was prepared in the same manner as in Example 1, except that the solvent was changed to "YS200" (hydrocarbon-based, boiling point 232°C, viscosity 50 mPa·s, manufactured by Yamaichi Chemical Industry Co., Ltd.). The viscosity of the conductive binder was 30 Pa·s. The conductive binder was in a state in which nylon fine particles and conductive particles were dispersed in the solvent. An attempt was made to prepare a probe sheet in the same manner as in Example 1, but it was not possible to form conductive bumps on the FPC by screen printing, and the probe sheet could not be prepared.

[0065] <Comparative Example 2> A conductive binder was prepared in the same manner as in Example 1, except that an SEBS polymer (Tuftec M1913, Asahi Kasei Corporation) was prepared as a binder, "YS200" was prepared as a solvent, and the conductive particles were added after SEBS was dissolved in the solvent. The conductive binder was in a state in which conductive particles were dispersed in the solvent in which the polymer was dissolved. A probe sheet was also produced in the same manner as in Example 1. The viscosity of the conductive binder was 30 Pa s. The conductive bumps formed from the conductive binder were in a state in which conductive particles were dispersed in the SEBS polymer while being partially in contact with each other.

[0066] Then, a continuity test was performed in the same manner as in Example 1. Table 1 shows the presence or absence of damage to the solder bumps after the continuity test, and the continuity resistance values ​​before and after the durability test.

[0067] <Comparative Example 3> As an elastomer, two-component liquid silicone (TSE3032A / B, Momentive) parts A and B were mixed in a ratio of 10:1, and conductive particles were mixed in a ratio of 200 parts by mass for 100 parts by mass of this silicone resin to prepare a conductive binder. The viscosity of the conductive binder was 40 Pa s. The conductive binder was in a state where conductive particles were dispersed in liquid silicone rubber.

[0068] Using this conductive binder, a probe sheet was produced in the same manner as in Example 1. The conductive bumps formed from the conductive binder were in a state in which conductive particles were dispersed in silicone rubber while being partially in contact with each other. Then, a continuity test was carried out in the same manner as in Example 1. Table 1 shows the presence or absence of damage to the solder bumps after the continuity test, and the continuity resistance values ​​before and after the durability test.

[0069] [Table 1]

[0070] Conductive bumps could not be formed on the FPC by screen printing in Comparative Example 1. This is thought to be because the dispersion only contained a low-viscosity solvent as a liquid component, making it impossible to transfer to the FPC.

[0071] In Comparative Examples 2 and 3, the binder component became a uniform liquid with an appropriate viscosity, making it possible to form conductive bumps on FPCs by screen printing. However, the conductive bumps formed by this method failed the durability test because the binder component was a relatively weak material such as elastomers such as SEBS or silicone rubber.

[0072] In Examples 1 and 2, a high viscosity type (viscosity 1000 mPa·s or more) was used as the conductive binder solvent, so even when fine particle nylon was used as the binder component, it was possible to form bumps on the FPC by screen printing. Good results were also obtained in tests using the formed conductive bumps. In addition, because high strength nylon was used as the binder component, good resistance values ​​were obtained even after durability tests. [Explanation of symbols]

[0073] 1 inspection probe sheet, 10 flexible sheet, 11a first surface, 11b second surface, 12 recess, 13 protrusion, 14 through electrode, 20 conductive bump, 30 semiconductor device, 31 bump, 40 wire probe

Claims

1. a flexible sheet having a through hole penetrating a first surface and a second surface, the through electrode being half-formed in the through hole, the flexible sheet having a recess recessed in the first surface; a conductive bump disposed in the recess, the conductive bump including polyamide having a flexural modulus of elasticity of 1300 MPa or more and 1600 MPa or less and a melting point of 160° C. or more and 200° C. or less, and conductive particles, the conductive particles being connected in a thickness direction of the flexible sheet; An electrical characteristic inspection jig comprising:

2. 2. The electrical characteristic inspection jig according to claim 1, wherein the total content of the polyamide and the conductive particles in the conductive bump is 85 wt % or more.

3. a step of forming a through electrode in a flexible sheet having a through hole penetrating a first surface and a second surface, the through hole having a recess recessed in the first surface; a filling step of filling the recess with a conductive binder including polyamide particles having a flexural modulus of 1300 MPa or more and 1600 MPa or less and a melting point of 160° C. or more and 200° C. or less and conductive particles; a heating step of melting the polyamide particles and connecting the conductive particles in a thickness direction of the flexible sheet; A method for manufacturing an inspection jig having the above structure.

4. 4. The method for manufacturing an inspection jig according to claim 3, wherein the viscosity of the conductive binder at 25° C. is 35 Pa·s or more and 60 Pa·s or less.

5. a bonding process for bonding an inspection probe sheet to an electrode surface of an object to be tested, the inspection probe sheet comprising a flexible sheet having a through-hole penetrating a first surface and a second surface, the through-hole having a half-formed through-electrode in the through-hole penetrating the first surface and a recessed portion recessed into the first surface, and a conductive bump disposed in the recessed portion, the conductive bump including polyamide having a flexural modulus of 1300 MPa or more and 1600 MPa or less and a melting point of 160°C or more and 200°C or less, and conductive particles, the conductive particles being connected in a thickness direction of the flexible sheet, and the conductive bump being brought into contact with an electrode of the object to be tested; an inspection step of pressing a probe against a through electrode from the other surface of the inspection probe sheet to inspect electrical characteristics; The electrical characteristic inspection method includes the steps of:

Citation Information

Patent Citations

  • Conductive resin composition

    JP2000345056A

  • Semiconductor device and manufacturing method thereof

    JP2001053184A

  • Method for manufacturing anisotropic conductive sheet

    JP2006024580A

  • Probe card, semiconductor inspection device, and method of manufacturing semiconductor device

    JP2009042008A

  • Inspection jig of electrical characteristic

    JP2018141652A